IMPLEMENTASI PROBLEM BASED LEARNING (PBL) BERBASIS LITERASI EKOLOGI UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA KELAS IV SEKOLAH DASAR - Rahayu, Anisya Pramitha; Aprilia Indah Cahyani; Adila Febrianti; Afiqa Aulia Aminah; Anisa Banowati Tri Dismaati; Angga Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low communication skills of elementary school students remain a challenge in 21st-century learning, highlighting the need for instructional models that encourage active student participation. This study aimed to improve the communication skills of fourth-grade elementary school students through the implementation of Ecology Literacy-Based Problem Based Learning (PBL). The study employed a Classroom Action Research (CAR) method using Kurt Lewin’s model, conducted in two cycles involving 19 students of class IV-A at an elementary school in Bogor City. Data were collected through observation and tests and analyzed using descriptive comparative techniques. The results showed an improvement in students’ communication skills, with the average score increasing from 9.85 in the pre-cycle to 11.85 in Cycle I. This improvement also affected students’ learning outcomes, as indicated by the increase in learning mastery from 10% in Cycle I to 70% in Cycle II. The findings demonstrate that Ecology Literacy-Based PBL effectively improves students’ communication skills and learning outcomes.